STUDY SOIL DEVELOPMENT AND CLASSIFICATION IN ERBIL PROVINCE, KURDISTAN, IRAQ USING MATHEMATICAL INDICES - H. A. S. Razvanchy; M. A. Fayyadh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The study area located at Erbil province, Kurdistan, Iraq, seven pedons were elected. Twenty-one soil samples were collected in the study area. Different physiochemical and fertility indices have been used to determine the soils development, despite of generating interpolated maps for them. The results indicated that the low values of clay were found in the less pedon developed and argillic horizon existed in development pedons. Study soils were non-saline, slightly to moderately alkaline, and had relatively high bulk density values. Organic matter is concentrated at the soil surface. Considerable total carbonates are found in studied soils and have irregular distribution manner, as well as have high CEC values. Low C/N ratio due to highly decomposed organic matter. The active CaCO3/total CaCO3 increases with depth in all pedons, while, slightly fluctuated in one pedon. The ratio of total clay in BH /AH was found just in some pedons and more than (1) therefore these soils are considered development, and are more developed depending on the ratio of fine clay/total clay. Soils are classified into three groups the first was the least developed soils, the second group has the most development. Third group are intermediate in their development. Pedogenic processes included leaching, illuviation, eluviation, alkalization, humification, lessivage, desalinization, calcification, decomposition, and littering. Studied soils classified as Inceptisols and Mollisols.